Achieving High‐Performance Nondoped OLEDs with Extremely Small Efficiency Roll‐Off by Combining Aggregation‐Induced Emission and Thermally Activated Delayed Fluorescence. (10th February 2017) - Guo, Jingjing; Li, Xiang‐Long; Nie, Han; Luo, Wenwen; Gan, Shifeng; Hu, Shimin; Hu, Rongrong; Qin, Anjun; Zhao, Zujin; Su, Shi‐Jian; Tang, Ben Zhong
Abstract : Luminescent materials with thermally activated delayed fluorescence (TADF) can harvest singlet and triplet excitons to afford high electroluminescence (EL) efficiencies for organic light‐emitting diodes (OLEDs). However, TADF emitters generally have to be dispersed into host matrices to suppress emission quenching and/or exciton annihilation, and most doped OLEDs of TADF emitters encounter a thorny problem of swift efficiency roll‐off as luminance increases. To address this issue, in this study, a new tailor‐made luminogen (dibenzothiophene‐benzoyl‐9, 9‐dimethyl‐9, 10‐dihydroacridine, DBT‐BZ‐DMAC) with an unsymmetrical structure is synthesized and investigated by crystallography, theoretical calculation, spectroscopies, etc. It shows aggregation‐induced emission, prominent TADF, and interesting mechanoluminescence property. Doped OLEDs of DBT‐BZ‐DMAC show high peak current and external quantum efficiencies of up to 51.7 cd A −1 and 17.9%, respectively, but the efficiency roll‐off is large at high luminance. High‐performance nondoped OLED is also achieved with neat film of DBT‐BZ‐DMAC, providing excellent maxima EL efficiencies of 43.3 cd A −1 and 14.2%, negligible current efficiency roll‐off of 0.46%, and external quantum efficiency roll‐off approaching null from peak values to those at 1000 cd m −2 . To the best of the authors' knowledge, this is one of the most efficient nondoped TADF OLEDs with small efficiency roll‐off reported so far. Abstract : A highly efficient nondoped organic light‐emitting diode affording excellent maxima electroluminescence efficiencies of 43.3 cd A −1 and 14.2%, negligible current efficiency roll‐off of 0.46%, and external quantum efficiency roll‐off approaching null from peak values to those at 1000 cd m −2, is attained based on a robust luminogen featuring aggregation‐induced emission and thermally activated delayed fluorescence.